DEVELOPING BAGWA AS A REFERENCE BOOK ON NATIONALISM INTEGRATION IN TEACHING SOCIAL SCIENCE COURSES AT PNU SOUTH LUZON, PHILIPPINES - Roel V. Avila, - (2020)
(This dissertation entitled, Developing Bagwa as a Reference Book on Nationalism Integration in Teaching Social Science Courses at PNU South Luzon, Philippines by Roel V. Avila (1608399 P1175), with the guidance and supervision of Prof. Dr. Nana Supriatna, Prof. Dr. H. Abdul Azis Wahab, and Prof. Dr. Enok Maryani, is under the Program Study: Doctorate in Social Science Education at Universitas Pendidikan Indonesia). Nationalism integration in pedagogy necessitates references. PNU served as locale of the study in the development and validation of a reference book via Research and Development (R&D). Through needs assessment, instrument validation, and assessment by professors, pre-service and in-service teachers, the study yielded data via 54-item questionnaire on the acceptability of Bagwa. Results indicated the need for finalizing concept of nationalism, raising Filipino consciousness level, focusing on Filipino sentiments, maximizing talent utilization, and associating self to homeland. In developing national consciousness, sentiments, deeds, and identity, Bagwa was perfectly acceptable. Its utilization was highly recommended.